Finitude (numbered.) - Ng, Adar Ai Qing (2018)
This essay serves as a form of record of my thoughts, research, and influences I have done throughout the year leading up to its final form.This report contains the analyses, and understanding of my desire to capture and create specific images, sound, and space; my thought processes and the artists that inspired me to attempt art-making. The development of my final year project was an organic meander of understanding myself and, my history so that it may inform my next step.